2014
DOI: 10.4238/2014.january.17.17
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol, an activator of SIRT1, upregulates AMPK and improves cardiac function in heart failure

Abstract: ABSTRACT. Reduced AMP-activated protein kinase (AMPK) expression has been shown to play a significant role in the cardiac dysfunction in heart failure. This study was designed to examine the effect of resveratrol, a potent activator of silent information regulator (SIRT1), on cardiac function and AMPK expression in heart failure. Adult male rat left anterior descending arteries were ligated, and they were fed with either a regular diet or a diet enriched with resveratrol. Heart failure was produced by myocardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
73
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(76 citation statements)
references
References 30 publications
1
73
0
Order By: Relevance
“…In addition, Xuan et al performed left coronary artery ligation on mice and found that resveratrol (20 mg/kg/day for 42 days) decreased cardiac remodeling and increased survival following the MI [168]. Similar positive results were observed in rats treated with 2.5 mg/kg/day resveratrol for 16 weeks post-MI [169]. In this latter study, resveratrol treated rats had improved cardiac function, decreased mortality, and decreased B-type natriuretic peptide (BNP) serum levels, demonstrating that resveratrol protected against the development of MI-induced heart failure [170].…”
Section: Preclinical Studiessupporting
confidence: 65%
See 1 more Smart Citation
“…In addition, Xuan et al performed left coronary artery ligation on mice and found that resveratrol (20 mg/kg/day for 42 days) decreased cardiac remodeling and increased survival following the MI [168]. Similar positive results were observed in rats treated with 2.5 mg/kg/day resveratrol for 16 weeks post-MI [169]. In this latter study, resveratrol treated rats had improved cardiac function, decreased mortality, and decreased B-type natriuretic peptide (BNP) serum levels, demonstrating that resveratrol protected against the development of MI-induced heart failure [170].…”
Section: Preclinical Studiessupporting
confidence: 65%
“…In addition to the role of AMPK, SIRT1 has been implicated in the ability of resveratrol to promote autophagy. For instance, in a MI model in rats, resveratrol increased SIRT1 and AMPK expression, and in vitro studies indicated that inhibition of SIRT1 decreased AMPK levels [169]. Moreover, in mice pretreated with resveratrol, a decrease in infarct size coupled with an increase in deacetylated substrate (indicating SIRT1 activation) was observed following ischemia-reperfusion [164].…”
Section: Preclinical Studiesmentioning
confidence: 96%
“…As known, the activity of SIRT1 depended on NAD þ and NAM interacted with SIRT1 via binding at the C pocket to feedback inhibit NAD þ [11,12]. Immunofluorescence staining revealed that the SIRT1-knockdown effects of shSIRT1 mostly occurred in the nucleus of ph ESCs, whereas NAM distributed in the cytoplasm (Fig.…”
Section: Sirt1 Impacted P53 Transcriptional Activity and Apoptosis VImentioning
confidence: 87%
“…To further investigate the mechanism underlying the regulation of p53 by SIRT1 in ph ESCs, resveratrol (trans-3,4 0 ,5-trihydroxystilbene), was used as a potent activator of SIRT1 through AMP-activated protein kinase (AMPK) induction [11,12]. AMPKa2 was a crucial catalytic subunit from AMPK phosphorylation.…”
Section: Sirt1 Impacted P53 Transcriptional Activity and Apoptosis VImentioning
confidence: 99%
“…To date there are no clinical trials that have studied PPARα agonists as specific metabolic therapies in HF. Activators of the PPAR regulator SIRT-1 however, such as resveratrol (which also activates AMPK by inhibiting ATP synthase; Price, et al, 2012), have been tested in the pre-clinical setting and were found to reduce oxidative stress in failing hamster hearts (Tanno, et al, 2010) and improve cardiac function in rats subjected to arterial ligation (Gu, et al, 2014). It has been identified however, that overexpression of SIRT-1 can impair diastolic function and in fact may cause DCM (Kawashima, et al, 2011).…”
Section: Increased Fatty Acid Utilizationmentioning
confidence: 99%